Effect of dietary supplementation with a combination of probiotics, enzymes and yeast on the growth performance, carcass traits and gut morphology of commercial broiler chickens - SOREN, STEPHEN; Jitendra, Rahangdale Harshal; Roy, Barun; Patra, Gopal; Batabyal, Subhasis (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study assessed the impact of dietary supplementation with a combination of probiotics, enzymes, and yeast on the growth performance, carcass traits, and gut morphology of commercial broiler chickens. A total of 128 one-day-old mixed-sex commercial broiler chickens (Vencobb 400) were randomly divided into four dietary groups, each with four replicated pens (n=4) containing eight broiler chickens per pen. The dietary groups were: 1) basal diet without any growth promoter (C), 2) basal diet with Bacitracin methylene disalicylate (BMD) at 0.2g/kg (T1), 3) basal diet with a combination of probiotics, enzymes, and yeast at 0.3g/kg of feed (T2), 4) basal diet with a combination of probiotics, enzymes, and yeast at 0.3g/kg + BMD at 0.2g/kg (T3). Body weight, feed intake, and feed conversion ratios were monitored weekly for 35 days. Carcass traits and gut morphology were assessed at the end of the trial. The results indicated that the T3 group showed significantly higher average daily gain compared to the control group throughout the study period. Feed conversion ratio was significantly improved in the T2 and T3 groups compared to the control group (P
Keywords: Broiler chicken; Enzyme; Growth performance; Probiotic; Yeast